Successful management of large clerical operations : a guide to effective service transaction systems - Stankard, Martin F. (New York : McGraw Hill Education, 1981)
This book seeks to help managers and other professionals responsible for operating, improving, or studying large labor-intensive service organizations. The book is concerned with the mix of workers, procedures, machines (including computers), and especially management which renders service in retail, financial, governmental, and similar sectors. New concepts and techniques are offered as a reference and a guide for managers and systems analysts to double-check their thinking, to stimulate new and better approaches to system design, and to aid diagnosis and analysis of existing systems and problems. The use of computers in service organizations is not dealt with here although the potential for this use is vast. Computers and other information-handling tools are vital links in many service processing chains. At present, however, they rarely make up the whole chain.
Section 1. Service Transaction Systems -- Section 2. Four Management Responsibilities -- Section 3. Analysis and Planning tools -- Section 4. System Studies and Implementation of Improvement -- Section 5. Toward a More Scientific Understanding of service Operations.
Includes bibliographical references and index.
Keywords: OFFICE MANAGEMENT